The relationship between burnout, sense of coherence and job safety attitudes among nurses after coronavirus disease 2019 in China: a cross-sectional survey - Xue, Fang; Liu, Jing; Zhou, Tong; Li, Xiuchuan; Liu, Chunfang; Li, Xueer; Li, Shuoshuo; Ye, Ping; Zhang, Jing (Frontiers in Public Health, 2025)
ObjectiveTo investigate burnout, sense of coherence (SOC), and job safety attitudes among nurses in China after the coronavirus disease 2019 (COVID-19) pandemic.MethodsThis cross-sectional study included 302 front-line nurses from Fangcang shelter hospitals (FSHs) in China. Descriptive, univariate, Pearson’s correlation, and multiple linear regression analyses were conducted to analyze factors related to job safety attitudes of nurses toward FSHs.ResultsThe incidence of burnout among nurses in FSHs was 65.2%; 57.9% had a low level of SOC, the score for safety attitude was 74.47 (standard deviation = 13.33), and the agreement rate was 51%. Burnout was negatively correlated with SOC (r = −0.399, p < 0.01) and safety attitudes (r = −0.141, p < 0.05), and SOC was positively correlated with safety attitudes (r = 0.428, p < 0.01). Personal accomplishment, depersonalization, changes in working hours, manageability, and marital status explained 33.8% of the variance in work safety attitudes.ConclusionThis study investigated the levels of burnout, SOC, and safety attitudes among nurses after COVID-19 in Chinese FSHs for the first time, and analyzed the associated factors. The results are valuable for improving the quality of nursing safety as well as patient safety management in FSHs.